Characterization and Significance of Monocytes in Acute Stanford Type B Aortic Dissection. (15th May 2020) - Lu, Li; Tong, Yuanhao; Wang, Wenwen; Hou, Yayi; Dou, Huan; Liu, Zhao
Abstract : Acute aortic dissection (AAD) is one of the most common fatal diseases noted in vascular surgery. Human monocytes circulate in dynamic equilibrium and display a considerable heterogeneity. However, the role of monocytes in AAD remains elusive. In our recent study, we firstly obtained blood samples from 22 patients with Stanford type B AAD and 44 age-, sex-, and comorbidity-matched control subjects. And the monocyte proportions were evaluated by flow cytometry. Results showed that the percentage of total CD14 + monocytes in the blood samples of Stanford AAD patients was increased significantly compared with that of normal volunteers (P < 0.0005 ), and the absolute numbers of CD14 bright CD16 + and CD14 bright CD16 - monocytes both increased significantly regardless of the percentage of PBMC or CD14 + cells, while CD14 dim CD16 + monocytes displayed the opposite tendency. However, the percentage of CD14 + cells and its three subsets demonstrated no correlation with D-dimer (DD) and C-reactive protein (CRP). Then, blood mononuclear cell (PBMC) samples were collected by Ficoll density gradient centrifugation, followed with CD14 + magnetic bead sorting. After the purity of CD14 + cells was validated over 90%, AAD-related genes were concentrated in CD14 + monocytes. There were no significant differences observed with regard to the mRNA expression levels of MMP1 (P = 0.0946 ), MMP2 (P = 0.3941 ), MMP9 (P = 0.2919 ), IL-6 (P = 0.4223 ), and IL-10 (P = 0.3375 ) of the CD14 + monocytes in Stanford type B AAD patients compared with those of normal volunteers. The expression levels of IL-17 (P < 0.05 ) was higher in Stanford type B AAD patients, while the expression levels of TIMP1(P<0.05), TIMP2(P<0.01), TGF-β1 (P < 0.01 ), SMAD3 (P < 0.01 ), ACTA2 (P < 0.001 ), and ADAMTS-1 (P < 0.001 ) decreased. The data suggested that monocytes might play an important role in the development of Stanford type B AAD. Understanding of the production, differentiation, and function of monocyte subsets might dictate future therapeutic avenues for Stanford type B AAD treatment and can aid the identification of novel biomarkers or potential therapeutic targets for decreasing inflammation in AAD.